2018
DOI: 10.1089/neu.2017.5453
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sex Differences and Hormonal Contraception on Outcomes after Collegiate Sports-Related Concussion

Abstract: There is conflicting evidence regarding whether females are more adversely affected after concussion than males. Further, recent research suggests that hormonal contraceptive (HC) use may affect symptom severity and duration post-concussion. The objective of this study was to examine the effects of sex and HC use on outcomes following concussion among collegiate varsity athletes. We hypothesized that females would have longer length of recovery (LOR), and that peak symptom severity would be associated with lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 44 publications
6
53
1
Order By: Relevance
“…Previous studies commonly report increased SRC incidence in female contact sports when compared to males, which was not supported by our present data. In addition, females typically fare worse than males after SRC . Both initial symptoms and duration of symptom are commonly worse, findings supported by our present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies commonly report increased SRC incidence in female contact sports when compared to males, which was not supported by our present data. In addition, females typically fare worse than males after SRC . Both initial symptoms and duration of symptom are commonly worse, findings supported by our present study.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, females typically fare worse than males after SRC. [36][37][38] Both initial symptoms and duration of symptom are commonly worse, 36 findings supported by our present study. The reasons for this gender difference are not established, although less neck muscle strength or biomechanical factors have been suggested.…”
supporting
confidence: 87%
“…However, a meta‐analysis of animal neuroscience research concluded that female mice displayed no more variability than males, and emphasized the suitability of their inclusion (Prendergast, Onishi, & Zucker, ). Using only male animals disregards the diverse response in outcome of mTBI in males and females (Gallagher et al, ). In the reviewed studies comparing sex differences in mTBI, differences were seen in male and female prefrontal cortex atrophy; white matter integrity in the corpus callosum; microglial activation; brain mRNA expression of GFAP, MBP, and tau; short‐term working memory; depressive‐like behavior; and social interaction (Hehar, Yu, Ma, & Mychasiuk, ; Mychasiuk, Hehar, et al, ; Wright, O'Brien, Shultz, & Mychasiuk, ; Yamakawa, Lengkeek, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that collegiate female athletes on hormonal contraceptives had significantly lower post-concussive symptom severity than females not on hormonal contraceptives 6 . Others have shown that menstrual cycle phase and contraceptive use at time of mTBI differentially affects post-concussive symptoms and quality of life one-month post-injury 13 .…”
Section: Introductionmentioning
confidence: 95%
“…However, this research has been conducted almost entirely among males 5 . Studying female athletes is crucial because evidence suggests adolescent females are more vulnerable to injury, experience a greater number of injuries and longer recovery from mTBI relative to males 69 . The limited mTBI studies that have included females, have not examined or controlled for female-specific factors such as contraceptive use, hormonal fluctuations, or menstrual cycle (MC) phase at time of injury or assessment 5,1012 .…”
Section: Introductionmentioning
confidence: 99%